Impact of headache disorders in Italy and the public-health and policy implications: a population-based study within the Eurolight Project - Allena, M.; Steiner, T. J.; Sances, G.; Carugno, B.; Balsamo, F.; Nappi, G.; Andrée, C.; Tassorelli, C. (The Journal of Headache and Pain, 2015)
Migraine, tension-type headache (TTH) and medication-overuse headache (MOH) are disabling lifelong illnesses. The Eurolight project, a partnership activity within the Global Campaign against Headache, assessed the impact of headache disorders in ten countries in Europe using a structured questionnaire coupled with various sampling methods. Here we present the findings from the Italian population.